Peran Advokasi Serta Bantuan Hukum Dalam Perlindungan Santri yang Mendapatkan Kekerasan di Pondok Pesantren - Ismaidar, Ismaidar; Nasution, Ahmad Ridwan; Dhillon, Erick Singh (Jurnal Ilmiah Penegakan Hukum, 2025)
Violence against students in Islamic boarding schools (pesantren) is a phenomenon that requires serious attention, considering that Islamic boarding schools are religious-based educational institutions that are supposed to uphold moral values, ethics, and the protection of human rights. This study aims to analyze the role of advocacy and legal aid in providing legal protection for students who are victims of violence in Islamic boarding schools. The research method used is normative juridical research with a legislative approach and a sociological approach, through literature study and field data collection in the form of interviews and documentation. The results of the study indicate that advocacy and legal aid play a crucial role in ensuring the fulfillment of the rights of students as victims, both in the reporting process, legal assistance, and psychological recovery. However, their implementation still faces various obstacles, including a lack of legal understanding in Islamic boarding schools, the existence of strong power relations, and stigma against victims. Therefore, it is necessary to strengthen the role of legal aid institutions, increase legal awareness, and synergy between Islamic boarding schools, law enforcement officials, and the community to realize effective and equitable legal protection for students who are victims of violence.